A novel vibration-assisted slurry impregnation to fabricate Cf/ZrB2-SiC composite with enhanced mechanical properties. Issue 4 (April 2019) - Hu, Ping; Zhang, Dongyang; Dong, Shun; Qu, Qiang; Zhang, Xinghong
Abstract: The three dimensional needle-punched carbon fiber reinforced ZrB2 -SiC composite (Cf /ZrB2 -SiC) with highly uniform distribution was fabricated successfully via a novel vibration-assisted slurry impregnation and low-temperature (1450 °C) hot pressing technique using nanosized ZrB2 powders. The carbon fiber/ceramic matrix interfaces were clear without obvious reaction products detected by the high resolution transmission electron microscopy (HR-TEM), indicating the degradation of carbon fiber was effectively inhibited. The Cf /ZrB2 -SiC composite exhibited a typical non-brittle fracture feature with a high work of fracture of 1104 J/m 2, which was approximately twice that of composite fabricated only by slurry impregnation and hot pressing. The enhancement in work of fracture was attributed to multiple toughening mechanisms of continuous carbon fibers such as extensive fiber bridging and pull-out accompanied by obvious crack deflection and branching. This work provides a valuable potential of preparing continuous carbon fiber reinforced ceramic composites with uniform component distribution and enhanced mechanical properties.